2023
DOI: 10.3390/gels9040265
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Peptide SCIBIOIII Hydrogel for Three-Dimensional Cell Culture That Promotes Wound Healing in Diabetic Mice

Abstract: An important clinical challenge is improving the healing rate of diabetic chronic wounds, and developing new approaches that can promote chronic wound healing is essential. A new biomaterial that has demonstrated great potential for tissue regeneration and repair is self-assembling peptides (SAPs); however, they have been less studied for the treatment of diabetic wounds. Here, we explored the role of an SAP, SCIBIOIII, with a special nanofibrous structure mimicking the natural extracellular matrix for chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Lu et al similarly explored using the SAP SCIBIOIII to form a special nanofiber structure mimicking the natural ECM in chronic diabetic wound repair. They showed that the SCIBIOIII hydrogel had good in vitro biocompatibility and could create a 3D culture microenvironment for continuous spherical skin cell growth [ 40 ]. In addition, the SCIBIOIII hydrogel significantly improved wound closure, collagen deposition, and tissue remodeling and enhanced chronic wound angiogenesis in diabetic mice.…”
Section: Application Of Sasp Hydrogels In Regenerative Medicinementioning
confidence: 99%
“…Lu et al similarly explored using the SAP SCIBIOIII to form a special nanofiber structure mimicking the natural ECM in chronic diabetic wound repair. They showed that the SCIBIOIII hydrogel had good in vitro biocompatibility and could create a 3D culture microenvironment for continuous spherical skin cell growth [ 40 ]. In addition, the SCIBIOIII hydrogel significantly improved wound closure, collagen deposition, and tissue remodeling and enhanced chronic wound angiogenesis in diabetic mice.…”
Section: Application Of Sasp Hydrogels In Regenerative Medicinementioning
confidence: 99%
“…GDF5 plays an important role in the formation and development of bones, joints, and neurons during human growth and development. Furthermore, it has a positive effect on skin healing and recovery [ [37] , [38] , [39] ]. Therefore, GDF5 has extensive application prospects in the medical field, especially in the field of regenerative medicine, such as bone and joint repair and nerve injury repair [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%